Prevalence of antibodies to Toxoplasma gondii in horses in the province of Kars, Turkey - A. Akca; C. Babur; Arslan MO; Y. Gicik; M. Kara; S. Kilic (Veterinární Medicína, 2004)
This study investigates the seroprevalence of Toxoplasma gondii in horses from seven villages in the province of Kars in north-eastern Turkey. A total of 189 serum samples from clinically healthy, local crossbred horses were tested for anti-T. gondii antibodies using the Sabin-Feldman dye test. Antibodies to T. gondii were found in 39 (20.6%) horses, with specific titres of 1 : 16 (27), 1 : 64 (11) and 1 : 256 (1). The 95% confidence interval for the population proportion ranged from 13.3 to 27.9%. The number of seropositive horses in Yucelen village (40%) was considerably higher than in other villages, whereas in the villages of Caglayan (8%) and Cerme (10.5%) the seroprevalence was lower than elsewhere. However, the differences in seroprevalence between the seven villages were not statistically significant (P > 0.05). In contrast, the overall seroprevalence in the province of Kars was significantly higher than that reported previously in studies carried out on army and private horse stud farms elsewhere in Turkey (P < 0.05). The relevance of these findings to the epizootiology of toxoplasmosis in Kars and Turkey is discussed.